Revision of the coral-inhabiting genus Conopea (Cirripedia: Archaeobalanidae) with description of two new species of the genera Conopea and Acasta - Kolbasov, Gregory A.; Chan, Benny K.k.; Molodtsova, Tina N.; Achituv, Yair (Zootaxa, 2016)
The morphology of archaeobalanid barnacles of the genera Conopea and Acasta inhabiting cnidarians of the orders Alcyonacea and Antipatharia was surveyed. Based on morphological characteristics, it became evident that the species of the nominal genus Conopea fell into three natural groups affiliated to three archaeobalanid genera, Conopea s.s., Acasta and Solidobalanus. The relationships between the species of Conopea s.l. and those of Acasta inhabiting alcyanaceans are analyzed using a cladistic approach. The barnacles of the genus Conopea s.s. are characterized by a strong, firm shell; the orifice is not dentate; rostral and sometimes carinal plates are often elongated in their basal parts; the rostro-carinal axis of the basis is often elongated and clasps the axis of the host coral; the radii have summits parallel to the basal margin of the parietes, and denticulated sutural margins; the scutum has simple growth ridges without longitudinal striation or ribs; the basitergal angle is truncated (sinusoid); and the basidorsal point of the penis is developed. The genus Conopea s.s. encompasses 20 epizoic species from tropical and temperate seas, inhabiting alcyonaceans (sea fans or gorgonians) and antipatharians. A new species of Conopea and a new species of Acasta are described, and a key to the species of Conopea s.s. is provided.